Integrality in cervical cancer care: evaluation of access - Brito-Silva, Keila; Bezerra, Adriana Falangola Benjamin; Chaves, Lucieli Dias Pedreschi; Tanaka, Oswaldo Yoshimi (Revista de Saúde Pública, 2014)
OBJECTIVE To evaluate integrity of access to uterine cervical cancer prevention, diagnosis and treatment services. METHODS The tracer condition was analyzed using a mixed quantitative and qualitative approach. The quantitative approach was based on secondary data from the analysis of cytology and biopsy exams performed between 2008 and 2010 on 25 to 59 year-old women in a municipality with a large population and with the necessary technological resources. Data were obtained from the Health Information System and the Regional Cervical Cancer Information System. Statistical analysis was performed using PASW statistic 17.0 software. The qualitative approach involved semi-structured interviews with service managers, health care professionals and users. NVivo 9.0 software was used for the content analysis of the primary data. RESULTS Pap smear coverage was low, possible due to insufficient screening and the difficulty of making appointments in primary care. The numbers of biopsies conducted are similar to those of abnormal cytologies, reflecting easy access to the specialized services. There was higher coverage among younger women. More serious diagnoses, for both cytologies and biopsies, were more prevalent in older women. CONCLUSIONS Insufficient coverage of cytologies, reported by the interviewees allows us to understand access difficulties in primary care, as well as the fragility of screening strategies.